2021
DOI: 10.3390/foods10092137
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Chemical Composition and Physicochemical Properties of the Mucilage Extracted from Fresh and Dehydrated Opuntia ficus indica Cladodes

Abstract: The development of sustainable extraction methods to obtain natural products constitutes a challenge for the food industry. The aim of this work was to compare yield, separation efficiency, chemical composition, and physicochemical properties of the mucilage extracted from fresh cladodes (FNM) and mucilage extracted from dehydrated cladodes (DNM) of O. ficus indica. Suspensions of fresh and dehydrated cladodes (4% w/w) were prepared for mucilage extraction by using a mechanical separation process. Subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 81 publications
4
11
3
Order By: Relevance
“…In all treatments, white granules were observed that are probably oxalate crystals. These crystals have already been reported in microwavedried nopal cladodes (Cruz-de la Cruz et al, 2020) and hot air (Quintero-García et al, 2021). The presence of these small crystals on the surface can be caused by the transport of mucilage, which occurs from the inside to the outside, during the drying process.…”
Section: Structural Analysismentioning
confidence: 65%
See 1 more Smart Citation
“…In all treatments, white granules were observed that are probably oxalate crystals. These crystals have already been reported in microwavedried nopal cladodes (Cruz-de la Cruz et al, 2020) and hot air (Quintero-García et al, 2021). The presence of these small crystals on the surface can be caused by the transport of mucilage, which occurs from the inside to the outside, during the drying process.…”
Section: Structural Analysismentioning
confidence: 65%
“…On average the moisture of fresh cladode was 14.3 ± 0.39 g H2O g −1 db (93.85±0.43 %). The moisture content for nopal has been reported within this range (Cruz-de la Cruz, Espinosa-Solares, Aguilar-Méndez, Guerra-Ramírez, & Hernández-Eugenio, 2020; Dey et al, 2019;Quintero-García et al, 2021). Table 2 shows the apical, basal, and average thickness of the cladodes before being subjected to the drying process.…”
Section: Characteristics Of Cladodementioning
confidence: 89%
“…Conversely, FM contains a high xylose and arabinose content. The protein content of the OFI extract is lower than that of FM but the higher ash content and especially calcium [47,48] could generate a pozzolanic reaction helping the microstructure.…”
Section: Discussionmentioning
confidence: 94%
“…The FT-IR spectral analysis ( Fig. 2 ) reveals various absorption peaks, each corresponding to specific molecular vibrations [ 14 , [19] , [20] , [21] ]. Within the range of 3700–2500 cm −1 , a broad absorption band is observed, indicating the intramolecular vibrational stretching of the –OH groups, which are extensively engaged in hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%